Does a Local Bias Exist in Equity Crowdfunding? - Lars Hornuf; Matthias Schmitt; Eliza Stenzhorn (Center for Economic Studies and ifo Institute (CESifo), 2020)
We use hand-collected data of 20,460 investment decisions and two distinct portals to analyze whether investors in equity crowdfunding direct their investments to local firms. In line with agency theory, the results suggest that investors exhibit a local bias, even when we control for family and friends. In addition to the regular crowd, our sample includes angel-like investors, who invest considerable amounts and exhibit a larger local bias. Well-diversified investors are less likely to suffer from this behavioral anomaly. The data further show that portal design is important for attracting investors more prone to having a local bias. Overall, we find that investors who direct their investments to local firms more often pick start-ups that run into insolvency or are dissolved, which indicates that local investments in equity crowdfunding constitute a behavioral anomaly rather and a rational preference. Here again, however, portal design plays a crucial role.
Keywords: G11; G24; K22; M13; 330; equity crowdfunding; crowdinvesting; local bias; individual investor behavior; entrepreneurial finance